PENGARUH MOTIVASI DAN MINAT TERHADAP HASIL BELAJAR MATEMATIKA PADA POKOK BAHASAN PERSAMAAN LINEAR SATU VARIABEL PADA SISWA KELAS VII SMP NEGERI 9 PADANGSIDIMPUAN - Yanti Novita Sitompul; Mohd. Arifin; Nurdalilah Nurdalilah (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2021)
One thing that must be developed in learning mathematics is students' motivation and interest in learning, because motivation and interest in learning have an important role in determining student success. This study aimed to determine whether there is an effect of student motivation and interest in learning on learning outcomes on the subject of linear equations of one variable. The population in this study were seventh grade students of SMP Negeri 9 Padangsidimpuan, with a total of 8 classes of VII class. In this study, the sample was taken from the population using the Cluster Random Sampling technique, namely the research took the sample based on a predetermined population area. The number of samples is 32 students. The data collection method used in this study is a questionnaire and documentation method. For the final data analysis using multiple Linear Regression. The results of the study obtained that the estimation equation for multiple linear regression for all students was = 39 + 0.79 + 1.02 with a partial correlation coefficient of 0.490, indicating a relationship between student motivation and learning outcomes in mathematics. The positive correlation coefficient value indicates that the relationship between motivation and learning outcomes is unidirectional. Partial correlation coefficient of 0.293, this indicates a relationship between student interest in mathematics learning outcomes. The positive correlation coefficient value indicates that the relationship between interest and learning outcomes is unidirectional. After the partial correlation coefficient was tested for significance, it turned out that both coefficients were significant, meaning that the relationship between student motivation and learning outcomes in mathematics if interest remained significant.